Catalytic pyrolysis of tulip tree (Liriodendron) in bubbling fluidized-bed reactor for upgrading bio-oil using dolomite catalyst. (1st November 2018) - Ly, Hoang Vu; Lim, Dong-Hyeon; Sim, Jae Wook; Kim, Seung-Soo; Kim, Jinsoo
Abstract: Fractional catalytic pyrolysis is an updated pyrolysis method, in which the biomass can be converted into higher quality bio-oil by upgrading the pyrolysis vapor in fluidized bed. In this study, the fast pyrolysis of tulip tree ( Liriodendron ) was performed in a bubbling fluidized-bed reactor under various reaction conditions (pyrolysis temperature, flow rate of fluidizing medium, and biomass particle size) to investigate the effects of these parameters on product yield and bio-oil quality. The system used silica sand and dolomite as the fluidizing bed material, and nitrogen as the fluidizing medium. When the pyrolysis temperature increased from 400 °C to 550 °C, the bio-oil yield was between 40.07 wt% and 49.03 wt% compared to those of 28.38 and 44.83 wt% using dolomite catalyst. Deoxygenation of bio-oil mostly produced water, and produced lower amounts of CO and CO2, but higher amounts of H2 and hydrocarbons gas. The catalytic process obtaineda high ratio of H2 /CO in the gas product. Highlights: Pyrolysis of tulip tree in fluidized bed reactor under different conditions. Catalytic pyrolysis using dolomite catalyst for upgrading bio-oil's quality. Dolomite rejected oxygen from pyrolysis vapor, mostly through dehydration. The catalytic process produced high H2 /CO ratio in the gas product.